KELANGSUNGAN HIDUP DAN PERTUMBUHAN BENIH IKAN GABUS (Channa striata) YANG DIBERI IKAN RUCAH BERBEDA SEBAGAI PAKAN - Muhamad Syarliandi Kusuma; Ade Dwi Sasanti; Yulisman . (Universitas Sriwijaya, 2017)
ABSTRACT Snakehead (Channa striata) is carnivorous fish that requires a source of nutrients from animal. Trash fish is one of alternative feed that can be used to rearing snakehead. This research aims to determine survival rate and growth of snakehead fry feeding by trash fish. This research is conduct on June- July 2016 in the Laboratorium Budidaya Perairan, Aquaculture Study Program. The research is design using Completely Randomized Design (CRD) consist of five treatments that are freshwater trash fish 100% (P1), marine trash fish 100% (P2), freshwater trash fish 75% : marine trash fish 25% (P3), freshwater trash fish 50% : marine trash fish 50% (P4), and freshwater trash fish 25% : marine trash fish 75% (P5). The parameters to be observed were survival rate, growth, feed efficiency and water quality. Based on the research results indicate (P4) the survival rate, growth absolutly length, absolutly weight and feed efficiency are significantly different. (P4) trash fish 50%: marine trash fish 50% diet is show highest value of survival rate, growth absolutly length, absolutly weight and feed efficiency are respectively 83.33%, 1.90 cm, 0.500 g and 71.93%. Water quality of rearing measurements during the research were temperature 28.8-29.7°C, pH 6.5-7.9, dissolved oxygen 4.50-5.27 mg.L-1 and ammonia 0.09- 0.24 mg.L-1. Water quality parameters were still support for rearing of snakehead fry. Keywords : Snakehead, Freshwater trash fish, Marine trash fish